The interactive effects of pST and salbutamol on the lysine requirement of finishing pigs - J A Hansen; J L Laurin; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1991)
A metabolism study was conducted to evaluate the interactive effects of daily pST injections and the Î²-agonist salbutamol on the lysine requirement of finishing pigs based on nitrogen retention. Sixteen finishing pigs (137 lbs initially) were exposed to one of four biological treatments for 32 d. These treatments were: 1) non-treated control; 2) 4 mg/d pST; 3) 2.75 ppm of dietary salbutamol; 4) both salbutamol and pST. Pigs were kept on the same biological treatment and offered one of four diets for an 8 d period in a Latin square arrangement. Diets were formulated to contain .8, 1.2, 1.6, and 2.0% dietary lysine, the assumed first-limiting amino acid. Pigs were acclimated to each diet for a 4 d period, after which feces and urine were collected for 4 d to evaluate nitrogen retention. Results indicate that the Î²-agonist salbutamol increased the daily feed consumption, daily gain, and the efficiency of gain; whereas pST injection reduced feed consumption and increased efficiency of gain. No interaction occurred between pST and salbutamol for percent nitrogen retention; however, pigs injected with pST and fed salbutamol had a higher daily nitrogen retention because of an increased nitrogen intake and improved nitrogen utilization. Pigs treated with pST had leaner carcasses with a higher percent muscle than non-treated controls or pigs fed salbutamol. These data suggest that pigs injected with pST have a dietary lysine requirement between 1.2 and 1.6%, whereas those fed salbutamol have a requirement similar to that of non-treated pigs, which may be confounded with increased daily feed intake. Pigs treated with both pST and salbutamol appear to have a lysine requirement slightly lower than that of pigs injected with pST alone, which appears to be due to increased feed intake.; Swine Day, Manhattan, KS, November 21. 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; G-F; Lysine; Repartitioning; Hormone